Targeted tumor therapy by epidermal growth factor appended toxin and purified saponin: An evaluation of toxicity and therapeutic potential in syngeneic tumor bearing mice. Issue 3 (28th December 2012) - Thakur, Mayank; Mergel, Katharina; Weng, Alexander; von Mallinckrodt, Benedicta; Gilabert-Oriol, Roger; Dürkop, Horst; Melzig, Matthias F.; Fuchs, Hendrik
Abstract : Targeted toxin‐based therapeutics are hindered by poor intracellular uptake, limited stability and non‐specific immune stimulation. To address these problems, ligand‐targeted toxins in combination with low dose saponin mixtures have been adapted and tested in vivo in the past, however, undefined saponin raw mixtures are not suitable for use in clinical development. In the present work we therefore used a targeted toxin (Sap3‐EGF, i.e. saporin fused to epidermal growth factor) in combination with a structurally defined isolated saponin m/z 1861 (SO‐1861). In vitro evaluation confirmed a 6900‐fold enhancement in the cytotoxic efficacy of Sap3‐EGF against TSA‐EGFR target cells. The required dose of the targeted toxin was appreciably reduced and there was a highly synergistic effect observed. An ex vivo hemolysis assay showed no or very less hemolysis up to 10 μg/mL of SO‐1861. In the acute toxicity studies SO‐1861 was found to be non‐toxic up to a dose of 100 μg/treatment. The enzymes aspartate aminotransferase, alanine aminotransferase, and glutamate dehydrogenase did not show any statistically significant liver damage, which was further confirmed by histological examination. Additionally, creatinine was also similar to the control group thus ruling out damage to kidney. In vivo studies in a syngeneic BALB/c tumor model characterized by EGFR overexpression were done by applying 30 μg SO‐1861 and 0.1 μg Sap3‐EGF per treatment. A more than 90% reduction (p < 0.05) in the average tumor volume was observed by this combined therapy. Highlights: ► A 6900‐fold enhancement in the in‐vitro efficacy of targeted toxins. ► First report on usage of a purified saponin in‐vivo as enhancer of targeted toxin‐based tumor therapy. ► Reduced toxin dose with higher efficacy provides evidence for better translational research. ► Basis for testing in heterogenous tumor models and for numerous plant‐derived toxins.